2012
DOI: 10.1158/0008-5472.can-11-3733
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Monitoring of Rare Circulating Hepatocellular Carcinoma Cells in an Orthotopic Model byIn VivoFlow Cytometry Assesses Resection on Metastasis

Abstract: The fate of circulating tumor cells (CTC) is an important determinant of metastasis and recurrence, which leads to most deaths in hepatocellular carcinoma (HCC). Therefore, quantification of CTCs proves to be an emerging tool for diagnosing, stratifying, and monitoring patients with metastatic diseases. In vivo flow cytometry has the capability to monitor the dynamics of fluorescently labeled CTCs continuously and noninvasively. Here, we combine in vivo flow cytometry technique and a GFP-transfected HCC orthot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
116
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 129 publications
(119 citation statements)
references
References 41 publications
0
116
0
Order By: Relevance
“…As an integrated indicator based on peripheral lymphocyte, neutrophil, and platelets counts, the predictive value of the SII for tumor recurrence and metastasis might be elucidated by the function of the three kinds of cells, and the their close relationship with CTCs, which play an important role in the initiation of recurrence and metastases after surgery (29)(30)(31). The patients with an elevated preoperative SII usually have thrombocytopenia, neutrophilia, or lymphopenia, suggesting an elevated inflammatory status and weak immune response in patients.…”
Section: Discussionmentioning
confidence: 99%
“…As an integrated indicator based on peripheral lymphocyte, neutrophil, and platelets counts, the predictive value of the SII for tumor recurrence and metastasis might be elucidated by the function of the three kinds of cells, and the their close relationship with CTCs, which play an important role in the initiation of recurrence and metastases after surgery (29)(30)(31). The patients with an elevated preoperative SII usually have thrombocytopenia, neutrophilia, or lymphopenia, suggesting an elevated inflammatory status and weak immune response in patients.…”
Section: Discussionmentioning
confidence: 99%
“…The results of prior animal studies have suggested that trafficking of tumor cells via bloodstream is involved in the induction of metastatic disease (2)(3)(4)(5)(6). However, the evidence derived from animal models differs significantly from human cancer.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the sensitivity, a study combines in vivo flow cytometry technique and a green fluorescent protein-transfected hepatocellular carcinoma orthotopic metastatic tumor model to monitor CTC dynamics. With 1.8-fold higher sensitivity than conventional flow cytometry, this novel approach shows that CTC dynamics is correlated with tumor growth in the orthotopic tumor model while the number and size of distant metastases correspond to CTC dynamics [15].…”
Section: X-ray Imaging Technique and Flow Cytometrymentioning
confidence: 99%